A Reconnaissance Survey of the Fforest Vegetation in the Doon Valley with the Aid of Aerial Photographs - Es, E. Van (Indian Forester, 1972)
As part of an integrated survey of the Doon Valley and the surrounding hills a survey of the forest vegetation with the aid of aerial photograps was carried out in 1971. The photographs used were panchromatic black and white on a scale of 1:60,000. It was possible to distinguish 15 types of the aerial photographs. It was found that the major forest types of the area could easily be located even on photographs which were not very suited for this task. The areas of particular interest either for management or for instance for reforestation can be selected from the map prepared from the aerial photographs. It can, therefore, be expected that a reconnaissance survey is most of the time possible with the photographs available of the area. With the aid of a survey of this type it is possible to do further planning and have areas of particular interest rephotographed on a more suitable scale.